2019
DOI: 10.32872/cpe.v1i4.33548
|View full text |Cite
|
Sign up to set email alerts
|

Further Specifying the Cognitive Model of Depression: Situational Expectations and Global Cognitions as Predictors of Depressive Symptoms

Abstract: The cognitive model of depression assumes that depressive symptoms are influenced by dysfunctional cognitions. To further specify this model, the present study aimed to examine the influence of different types of cognitions on depressive symptoms, i.e., situational expectations and global cognitions. It was hypothesized that situational expectations predict depressive symptoms beyond global cognitions. The present study examined a clinical (N = 91) and a healthy sample (N = 80) using longitudinal dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Numerous factors that contribute to the etiology and maintenance of depression have been suggested (7), e.g., dysfunctional expectations (8,9). Moreover, these factors include skills deficits targeted by "third wave" behavioral therapies that are associated with depression but not captured by the existing diagnostic criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous factors that contribute to the etiology and maintenance of depression have been suggested (7), e.g., dysfunctional expectations (8,9). Moreover, these factors include skills deficits targeted by "third wave" behavioral therapies that are associated with depression but not captured by the existing diagnostic criteria.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the DES total score has shown excellent internal consistency as indicated by Cronbach's α (Kube et al, 2017, 2018, 2019). In the present sample, the internal consistency for the entire 25‐item DES was Cronbach's α = 0.86 at both T1 and T2.…”
Section: Methodsmentioning
confidence: 88%
“…and the intense emotions related to the trauma (e.g., "When I experience unpleasant emotions such as fear or guilt, I will feel helpless coping with these emotions."). Because studies showed that such disorder-specific expectations contribute incrementally to the development of depressive symptoms beyond other types of cognitions (Kube et al, 2019;Kube et al, 2018), we believe that it might be valuable to examine them in PTSD as well. Besides disorder-specific expectations, it might also be worthwhile to consider patients' treatment expectations (e.g., "If I confront myself with the traumatic event during therapy, I will feel much better in the longer run.…”
Section: Introductionmentioning
confidence: 99%
“…When aiming to assess relevant types of expectations in PTSD, one may consider symptom-specific expectations referring to the memory of the traumatic event (e.g., “When I am reminded of the traumatic event, I will feel like being at the mercy of these memories.”) and the intense emotions related to the trauma (e.g., “When I experience unpleasant emotions such as fear or guilt, I will feel helpless coping with these emotions.”). Because studies showed that such disorder-specific expectations contribute incrementally to the development of depressive symptoms beyond other types of cognitions (Kube et al, 2019; Kube et al, 2018), we believe that it might be valuable to examine them in PTSD as well. Besides disorder-specific expectations, it might also be worthwhile to consider patients’ treatment expectations (e.g., “If I confront myself with the traumatic event during therapy, I will feel much better in the longer run.”), as studies showed that such outcome expectations predict treatment response for combat veterans suffering from PTSD (Price et al, 2015).…”
mentioning
confidence: 99%